Noninvasive cardiac output monitoring in a porcine model using the inspired sinewave technique: a proof-of-concept study - Bruce, R; Crockett, D; Morgan, A; Tran, M; Formenti, F; Phan, P; Farmery, A (Elsevier, 2019)
Background Cardiac output monitoring can support the management of high-risk surgical patients, but the pulmonary artery catheterisation required by the current ‘gold standard’—bolus thermodilution —has the potential to cause life-threatening complications. We present a novel noninvasive and fully automated method that uses the inspired sinewave technique to continuously monitor cardiac output. Methods Over successive breaths the inspired nitrous oxide (N2O) concentration was forced to oscillate sinusoidally with a fixed mean (4%), amplitude (3%), and period (60 s). was determined in a single-compartment tidal ventilation lung model that used the resulting amplitude/phase of the expired N2O sinewave. The agreement and trending ability of were compared with during pharmacologically induced haemodynamic changes, before and after repeated lung lavages, in eight anaesthetised pigs. Results Before lung lavage, changes in and from baseline had a mean bias of –0.52 L min−1 (95% confidence interval [CI], –0.41 to –0.63). The concordance between and was 92.5% as assessed by four-quadrant analysis, and polar plot analysis revealed a mean angular bias of 5.98° (95% CI, –24.4°–36.3°). After lung lavage, concordance was slightly reduced (89.4%), and the mean angular bias widened to 21.8° (–4.2°, 47.6°). Impaired trending ability correlated with shunt fraction (r=0.79, P<0.05). Conclusions The inspired sinewave technique provides continuous and noninvasive monitoring of cardiac output, with a ‘marginal–good’ trending ability compared with cardiac output based on thermodilution. However, the trending ability can be reduced with increasing shunt fraction, such as in acute lung injury.